Migratory dependency and the death penalty: foreign nationals facing capital punishment in the Gulf - Harry, L; Hoyle, C; Hutton, J (SAGE Publications, 2023)
This article focuses on the cases of 664 foreign nationals, the majority of whom are migrant workers, under sentence of death across the Gulf states (including Jordan and Lebanon) between 2016 and 2021. The features of these cases suggest that they are inextricably linked to migrant workers’ dependency under the kafala system, with examples of migrants duped into smuggling drugs across the border by their migrant broker, and once in country, accounts of violent altercations due to disputes about exit visas, and in the case of migrant domestic workers, self-defence against sexual violence. Engaging with the burgeoning literature on immigration, exploitation and criminalisation, as well as scholarship on capital punishment, this article will explore the multiple and unique layers of dependency fostered by the kafala system that place migrant workers at higher risk of the death penalty in these Gulf jurisdictions.